2016
DOI: 10.3390/agronomy6010020
|View full text |Cite
|
Sign up to set email alerts
|

NRT2.4 and NRT2.5 Are Two Half-Size Transporters from the Chlamydomonas NRT2 Family

Abstract: Abstract:The NRT2 transporters mediate High Affinity Nitrate/NitriteTransport (HAN/NiT), which are essential for nitrogen acquisition from these inorganic forms. The NRT2 proteins are encoded by a multigene family in plants, and contain 12 transmembrane-spanning domains. Chlamydomonas reinhardtii has six NRT2, two of which (NRT2.5 and NRT2.4) are located in Chromosome III, in tandem head to tail. cDNAs for these genes were isolated and their sequence revealed that they correspond to half-size NRT2 transporters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This structure is also present in the predicted topology for ZosmaNRT2 with a central cytosolic loop of 31 amino acids (Figure 1). Furthermore, in all members of the NNP family, it has been experimentally shown that N and C-terminal domains and the central loop fall on the cytosolic side of the plasma membrane [33,34,35]. This feature is also preserved in the proposed topology for ZosmaNRT2 (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…This structure is also present in the predicted topology for ZosmaNRT2 with a central cytosolic loop of 31 amino acids (Figure 1). Furthermore, in all members of the NNP family, it has been experimentally shown that N and C-terminal domains and the central loop fall on the cytosolic side of the plasma membrane [33,34,35]. This feature is also preserved in the proposed topology for ZosmaNRT2 (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…In land plants, three different gene families of nitrate transporters have been identified, NRT1, NRT2, and NRT3 ( Plett et al., 2010 ), all of which symport NO 3 − and protons, with low or high affinity for NO 3 − ( Pinton et al., 2016 ). In addition, the genome of the unicellular green alga Chlamydomonas reinhardtii contains six NRT2 genes ( Higuera et al., 2016 ), and the unicellular red alga Porphyridium purpureum contains two NRT2 genes ( Figure 3 ). Therefore, the presence of a single-copy NRT2 gene ( Figure 2 ; Kakinuma et al., 2008 ; Brawley et al., 2017 ; Li et al., 2019b ) is unique to multicellular Bangiales.…”
Section: Resultsmentioning
confidence: 99%
“…Other transporters (NRT2. [3][4][5][6] in the NRT2 family are low-affinity nitrate transporters [36,39]. NAR1 transporters only play a role in nitrite and bicarbonate transportation; hence, we decided to choose NRT1, NRT2.1 and NRT2.2 genes from nitrate/nitrite transporter families for expression study as these three seem to play the role of the main nitrate transporters.…”
Section: Discussionmentioning
confidence: 99%